JUMLAH ERITROSIT DAN NILAI HEMATOKRIT SAPI ACEH DAN SAPI BALI DI KECAMATAN LEUMBAH SEULAWAH KABUPATEN ACEH BESAR (Total Erythrocytes Count and Haematocrit Value of Aceh and Bali Cattle in Leumbah Seulawah, Aceh Besar) - Mulyadi Adam; Triva Murtina Lubis; Baradillah Abdyad; Nuzul Asmilia; Muttaqien Muttaqien; Fakhrurrazi Fakhrurrazi (Universitas Syiah Kuala, 2015)
The aim of this research was to find out total erythrocytes count and hematocrit value of aceh and bali cattle in Leumbah Seulawah, Aceh Besar. Ten aceh cattle (5 males and 5 females with the age of 2.5-3.0 years) and ten bali cattle (5 males and 5 females aged 2.5-3.0 years) from Leumbah Seulawah, Aceh Besar were used in this research. Blood samples approximately 3 cc were collected by venoject through jugular vein. Erythrocyte counts were performed using a hemocytometer and hematocrit value were performed by microhematocrit method. The average of erythrocyte counts of male and female aceh cattle were 7.75 ±1.86 and 7.34±0.73 (106/mm3) respectively, while male and female bali cattle were 5.49±0.88 and 4.89±0.53 (106/mm3) respectively. Hematocrit value of male and female aceh cattle were 32.8±3.70 dan 32.6±207% respectively, while male and female bali cattle were 27.4±3.00 and 25.8±1.30% respectively. In conclusion, erythrocytes count and hematocrit value of aceh cattle show significant difference (P0.01) from bali cattle.Key words: erythrocytes, hematocrit, aceh cattle, bali cattle